Assessment of Β-Sitosterol in Capsicum Annuum Grossum: A Phytochemical Approach - Khamees, Amjed Haseeb; Nassir, Zahraa Suhai; Jasim, Ali Rahman (Scripta Medica, 2025)
Capsicum annuum Grossum Senise, a widely cultivated sweet pepper in Iraq contains a diverse array of bioactive compounds such as polyphenols, carotenoids and capsinoids, known for their beneficial effects on health. Among these, phytosterols structurally analogous to mammalian cholesterol are essential components of cellular structures of plants, where β-sitosterol predominates among sterol components. These sterols are primarily concentrated in lipid-dense botanical sources like nuts, seeds and legumes, exhibiting a wide range of pharmacological effects in experimental research. These include anxiolytic, pain relief, immune regulation, pathogen inhibition, tumour suppression, inflammation reduction, oxidative stress mitigation, as well as benefits for lipid metabolism, liver health and glucose control. This study focuses on the extraction, isolation, purification and quantitative analysis of β-sitosterol from Iraqi Capsicum annuum Grossum. The chloroform fraction exhibited a high β-sitosterol concentration (0.492 mg/mL dry weight), suggesting efficient biosynthesis of this secondary metabolite, possibly due to favourable biochemical and environmental factors. Advanced chromatographic and spectroscopic techniques were employed to ensure accurate quantification and structural characterisation. The findings underscore the potential of Iraqi-grown Capsicum annuum Grossum as a valuable source of β-sitosterol, supporting its use in nutraceutical and pharmaceutical applications. Further research is warranted to explore its mechanistic pathways and therapeutic efficacy in clinical settings.